Upaya Peningkatan Hasil Belajar Matematika pada Peserta Didik Kelas VIII di SMPN 1 Takeran Melalui Pembelajaran Berdiferensiasi - Retno Akmalia Az-Zahra; Sanusi Sanusi; Sri Handayani (Departement of Mathematics Education, 2024)
This research observation was motivated by the differences in cognitive abilities possessed by students at one of the schools in Magetan district, namely SMPN 1 Takeran and this observation aimed to determine the effect of implementing differentiated learning through the TaRL approach on the learning outcomes of class VIII students in quadrilateral material. This observation was carried out in class VIII C at SMP Negeri 1 Takeran for the 2023/2024 academic year. The observation subjects were 26 students. The method used in this observation is the classroom action observation method which consists of a pre-cycle and two cycles (cycle 1 and cycle 2). Observation results show that the application of differentiated learning through the Teaching at The Right Level approach can improve students' mathematics learning outcomes in quadrilateral material with the achievement of learning completeness which initially in the pre-cycle was 38.46% with 11 students above the KKM and then increased in the first cycle became 57.96% with 17 students above the KKM and increased again in the second cycle to 100% with all students above the KKM. So the observation was declared successful.